Impact of Duration of Smoking on Lung Function Parameters in Young Adult Males (International Journal of Physiology, 2020)
Background: The tobacco epidemic is one of the biggest public health threats the world has ever faced,killing more than 8 million people a year. In 2002, about 20% of young teens smoked worldwide, half ofthose who begin smoking in adolescent years are projected to go on to smoke for 15 to 20 years. Smokingincreases the risk of developing coronary artery disease, stroke, chronic obstructive pulmonary disease(COPD) and various malignancies. Smoking is being recognized as the most important causative factor forCOPD. While studies have shown an overall ‘dose response curve” for smoking and lung function, someindividuals develop severe disease within few years of smoking, whereas some individuals show minimalto no clinical symptoms even after many years of smoking. Hence the following cross sectional study wasundertaken to assess the extent of decline in lung function parameters with duration of smoking in youngadults with no apparent clinical features of COPD.Objectives: To assess the impact of duration of smoking on various lung function parameters in young adultmales.Materials and Method: Fifty apparently healthy, young smokers were selected for the study. Pulmonaryfunction test was evaluated by computerized spirometer (UNI-EM SPIROMIN). Correlation betweenduration of smoking and various lung function parameters was analyzed by ANNOVA.Results: All parameters were found to decline with duration of smoking, however the decline in FVC andFEV1 were statistically significant.Conclusion: Duration of smoking is correlated strongly with decline in FVC and FEV1 values.